1994
DOI: 10.1006/qres.1994.1005
|View full text |Cite
|
Sign up to set email alerts
|

Transport Direction of Wisconsinan Loess in Southeastern Minnesota

Abstract: A study of Wisconsinan loess in part of southeastern Minnesota confirms earlier suggestions that much of the loess in this region was not derived flora the floodplain of the Mississippi River. Two Wisconsinan loess units, the Peoria Loess and Roxana Silt, occur in the study area. Peoria Loess, 1-8 m thick, fines systematically eastward from an abrupt western border toward the Mississippi. There are no apparent grain-size trends away from other adjacent rivers. Peoria Loess thickness generally decreases eastwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…The poor performance of χ ped for Midwestern soils may be due to (1) variations in the underlying parent material and (2) additional dust input during the Holocene. Peoria loess, which is the parent material for our soil profiles, is relatively homogenous, but various studies [e.g., Mason et al , 1994; Muhs and Bettis , 2000; Muhs et al , 2008; Winspear and Pye , 1995] have identified several dust sources and transport paths. Geiss and Zanner [2007] have found significant variations in the magnetic properties of unaltered Peoria loess.…”
Section: Resultsmentioning
confidence: 99%
“…The poor performance of χ ped for Midwestern soils may be due to (1) variations in the underlying parent material and (2) additional dust input during the Holocene. Peoria loess, which is the parent material for our soil profiles, is relatively homogenous, but various studies [e.g., Mason et al , 1994; Muhs and Bettis , 2000; Muhs et al , 2008; Winspear and Pye , 1995] have identified several dust sources and transport paths. Geiss and Zanner [2007] have found significant variations in the magnetic properties of unaltered Peoria loess.…”
Section: Resultsmentioning
confidence: 99%
“…As the height of vegetation increases, the aerodynamic roughness height also increases, resulting in higher trapping efficiency (Tsoar and Pye, 1987). Sparse herb tundra with low trapping efficiency has been hypothesized to explain the lack of thick LGM loess in Alaska , but studies in the Great Plains suggest that thick loess accumulated on ridge tops during the LGM under or in proximity to herb tundra vegetation (Baker et al, 1999;Mason et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Three study sites occur on ridges adjacent to the Root River Valley in southeastern Minnesota (Fig. 1B) where sand deposits are found on multiple valley slopes and ridgetops that in most instances would be covered with up to 4 m of Peoria Loess (Mason et al, 1994). Where present, the Peoria Loess overlies a red clay-rich unit believed to be residuum from dolomite bedrock, but probably also containing older weathered loess units (Frolking et al, 1983;Jacobs et al, 1997;Mason and Knox, 1997).…”
Section: Geomorphic Settingmentioning
confidence: 97%